A novel multihoming-based flow mobility scheme to support mobility management in NEMO - Islam, Shayla; Hassan Abdalla Hashim, Aisha; Habaebi, Mohamed Hadi; Hassan, Wan Haslina; Hasan, Muhammad Kamrul (2014)
With Network Mobility Basic Support Protocol (NEMO BSP), each communication should pass via the Home Agents (HAs) of all Mobile Routers (MRs) earlier reaching their destination at the time of frequent movement among inter technology handoff. This eventually results in performance deterioration of the real time application scenarios conducting on Mobile Nodes (MNs). Accordingly, applying multihoming technique at any place, anywhere to provide uninterrupted Internet connection in NEMO is becoming a significant area for current researchers. Although Multiple Care of Address (MCOA) registration between MR along with its HA can overcome some of the multihoming issues for NEMO, but still required a dynamic flow redirection mechanism to support mobility management in NEMO. With the intention of reducing handoff delay, a novel Multihoming-based Flow mobility scheme on PMIPv6 domain in NEMO (MF-PNEMO) is proposed in this paper. In addition, the performance of the MF-PNEMO scheme is evaluated through numerical approach. The evaluation results confirms that MF-PNEMO scheme outperforms the standard NEMO BSP as well as Fast Proxy NEMO (FP-NEMO) concerning handoff delay during inter technology handoff.